Peran Komunitas Industri Pandai Besi dalam Meningkatkan Pendapatan Keluarga di Desa Ketapangkuning Kecamatan Ngusikan Kabupaten Jombang - Anita Jaya Wulandari; Rivo Nugroho (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
The blacksmith industry community in Ketapangkuning Village, Ngusikan District, Jombang Regency is a form of community economic activity with significant role in increasing family income. This study aims to analyze the role of the blacksmith industry community in increasing family income. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with 7 informants (blacksmith craftsmen, business owners, spouses of craftsmen, community leaders, and local residents), participant observation of daily production activities, and documentation of production processes and community records. Data analysis followed Miles and Huberman's interactive model through data reduction, data display, and conclusion drawing. Results indicate that the blacksmith industry community plays a key role through employment provision, household economic productivity improvement, and promotion of economic independence. Social solidarity is also reinforced through production cooperation among members. Family income increased by an average of 30% to 50% after joining the community. However, challenges remain in terms of capital limitations, raw material prices, and market competition. Support from local government in capital assistance, product innovation, and digital marketing development is highly needed to sustain and improve the competitiveness of this traditional industry.